State of soil conservation practices in Silti Woreda, Southern Ethiopia - Ali, Mushir; Surur , Kedru (Journal for Geography, 2012)
Soil erosion is the major problem of Ethiopian highland areas where an average soil loss of 42tons/ha/year, with rate soil depth loss of more than 2 cm/year, corresponding to 1 to 2 billion US/year (an amount comparable to the country’s annual budget). The higher soil loss has been estimated at Southern Ethiopia where densely settled on highlands. A vast majority of the population derives its livelihood from forest, livestock herding and agriculture. The economic conditions force the rural poor to exploit the environment for their survival. Keeping the importance, the work was conducted in Silti Woreda, Southern Ethiopia, with the objectives; to identify the current status and trend of soil conservation practices, to assess the socio-cultural, economic, biophysical and institutional/policy/support system constraints for the implementation and maintenance of conservation practices. The study reveals, indigenous soil conservation technologies are considered as effective methods of conservation. But, population poverty and unawareness are major constraints.